2005
DOI: 10.1007/s10103-005-0356-8
|View full text |Cite
|
Sign up to set email alerts
|

Elemental analysis of urinary calculi by laser induced plasma spectroscopy

Abstract: Laser induced plasma spectroscopy (LIPS) has been applied to analyse and identify elemental constituents of urinary calculi. Measurements on seven different urinary stone samples were conducted and the concentrations of some key elemental species were estimated. The elements detected with the present system were: Calcium, Magnesium, Sodium, Samarium, Potassium and Lead. Absolute concentrations of the species were derived from pre-calibration of the system for each element. Their concentrations were found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Fang et al 290 used the LIBS technique to analyze and identify elemental constituents of urinary calculi. The results showed that the elements detected with this study were: Ca, Mg, Na, Sr, K and Pb.…”
Section: Medical and Biological Applicationsmentioning
confidence: 99%
“…Fang et al 290 used the LIBS technique to analyze and identify elemental constituents of urinary calculi. The results showed that the elements detected with this study were: Ca, Mg, Na, Sr, K and Pb.…”
Section: Medical and Biological Applicationsmentioning
confidence: 99%
“…Fang et al [17] reported the first use of LIBS for urinary stone analysis. They analyzed seven urinary stone samples using both LIBS and Fourier transform infrared spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study support the results of the above-mentioned studies with respect to the reliability of LIBS. Furthermore, we used XRD for comparison, and our study had a larger number of patients than did that of Fang et al [17] Laser-induced breakdown spectroscopy has some advantages that make it a useful technique. One of these advantages is that prior sample preparation is not necessary, [17] while it is required for XRD and IRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIBS has been utilized to elementally characterize removed gallstones [25,26], kidney stones [27], and other urinary calculi (stones [28]). Rather than possessing a common composition, all of these stones occur in a wide variety of elemental concentrations and compositions, each uniquely identifiable via LIBS analysis.…”
Section: Dental/mineralized Tissuesmentioning
confidence: 99%